A New Approach to Persian Poetry Meters from Linguistics and Rhythm Viewpoints - mohamad mirzayi; Shahram Naghshbandi; Hosein Meisami; Yadollah Shokri (مطالعات زبانی و بلاغی)
This study investigates the rhythm in Persian poetry based on what Persian native speakers read and perceive, not based on current postulated metrical rules. The study has been done from the perspective of rhythm and linguistics (by parsing the stressed syllables). It is hypothesized that there is a difference between current postulated metrical rules of Persian poetry and the way it is read naturally by Persian native speakers. Fifty verses with different metrics from the 3rd to 15th century's poets were chosen based on their frequency of use in Persian poetry. Then they were given to 20 people who could read poetry correctly and they were recorded. Other than briefing and providing a sample, they were asked to tap on the tables rhythmically like what they do in clapping. Around 900 audio files were analyzed and the place of stress in syllables were determined. Some patterns were found through the analysis. Then the major patterns were picked based on their frequency. Based on the prominent pattern, the suggested parsing were proposed. It was indicated that Persian speakers perceive the alteration in verse initial metrics in addition to the alteration in verse final metrics. They do rhythmic parsing differently from the traditional postulated metrics. They keep reading different rhymes in iterative patterns. Therefore, it has been suggested that verses can be parsed based on the number of the short syllables, but not the number of syllables as hypothesized in traditional Persian metrics.